THE APPLICATION OF NUMBERED HEADS TOGETHER (NHT) METHOD USING GRAPHIC MEDIA IN IMPROVING NATURAL SCIENCE LEARNING FOR THE FOURTH GRADE STUDENTS OF SDN 1 CANGKREP LOR IN THE ACADEMIC YEAR OF 2014/2015. - Setyaningsih, Lilis (KALAM CENDEKIA PGSD KEBUMEN, 2015)
The objectives of this research are to describe the stages of the application of Numbered Heads Together (NHT) method using graphic media; to improve natural science learning about nature resource for the fourth grade students of SDN 1 Cangkrep Lor in the academic year of 2014/2015; and to describe problems and solutions. This research is collaborative classroom action research which conducted within three cycles. The subjects were the fourth grade students of SDN 1 Cangkrep Lor in the academic year of 2014/2015, amounting to 35 students. The sources of data were students, teacher, colleagues, researcher, and documents. The techniques of data collection were observation, interview, and test. The result of the research indicate that the application of Numbered Heads Together (NHT) method using graphic media implemented with appropriate stages can improve natural science learning about nature resource for the fourth grade students SDN 1 Cangkrep Lor in the academic year of 2014/2015.